Exploring the safety and quality of mobile X-ray imaging in a new infectious disease biocontainment unit: an in situ simulation and video-reflexive study - Chris Degeling; G L Gilbert; Cameron Moore; Su-yin Hor; Mary Wyer; Ruth Barratt; Leah Williams Veazey; Phillip Garrahy (BMJ Open, 2024)
Objectives During a precommissioning inspection of a new biocontainment centre, radiographers noted structural features of quarantine rooms that could compromise staff and patient safety and the X-ray image quality, even after significant modifications had been made to an earlier radiography protocol. The aim of this study was to explore the safety and effectiveness of the modified protocol, in the new space, and identify improvements, if required.Design A qualitative study using in situ simulation and video-reflexive methods.Setting A newly built biocontainment centre, prior to its commissioning in 2021, in a large, tertiary hospital in Sydney, Australia.Participants Five radiographers, and a nurse and a physician from the biocontainment centre, consented to participate. All completed the study.Interventions Two simulated mobile X-ray examinations were conducted in the unit prior to its commissioning; simulations were videoed. Participants and other stakeholders analysed video footage, collaboratively, and sessions were audio recorded, transcribed and analysed thematically. Problems and potential solutions identified were collated and communicated to the hospital executive, for endorsement and actioning, if possible.Results Four themes were identified from the data: infection exposure risks, occupational health and exposure risks, communication and X-ray image quality. Facilitated group reviews of video footage identified several important issues, across these four areas of risk, which had not been identified previously.Conclusions In situ simulation is used, increasingly, to evaluate and improve healthcare practices. This study confirmed the added value of video-reflexive methods, which provided experienced participants with a richer view of a familiar protocol, in a new setting. Video footage can be examined immediately, or later if required, by a broader group of stakeholders, with diverse experience or expertise. Using video reflexivity, clinicians identified potential safety risks, which were collated and reported to the hospital executive, who agreed to implement modifications.